Chronic Total Occlusion Revascularization Strategies: A Comparative Study of Percutaneous Coronary Intervention and Coronary Artery Bypass Grafting - Yanci Liu; Shaoping Wang; Hongyu Peng; Qian Fan; Jinghua Liu (Reviews in Cardiovascular Medicine, 2025)
Objective: Currently, there are limited data on the clinical outcomes of percutaneous coronary intervention (PCI) compared to coronary artery bypass grafting (CABG) for the treatment of chronic total occlusion (CTO). We compared the clinical outcomes of patients with CTO lesions treated by PCI versus CABG. Methods: This study included 2587 patients with coronary artery disease (CAD) with CTO from January 1, 2019 to December 31, 2021. Both short- and long-term clinical outcomes were compared in patients with CTO who received successful revascularization. The primary endpoint, defined as major adverse cardiac and cerebrovascular events (MACCE), was a composite of all-cause mortality, cerebrovascular events, and myocardial infarction. Unplanned revascularization and heart failure hospitalization were defined as secondary endpoints separately. Propensity score matching was applied to balance baseline characteristics between the two groups. Results: The PCI group had lower MACCE (0.47% vs. 2.11%) within 30 days of the index operation, but the difference did not reach statistical significance (p = 0.06). After an average follow-up of 37.2 months, no significant differences were observed between PCI and CABG in all-cause mortality (hazard ratio [HR] = 2.29, 95% CI: 0.79–6.61; p = 0.13), MACCE (HR = 2.03, 95% CI: 0.86–4.76; p = 0.10), or heart failure hospitalization rate (sub distribution HR [SHR] = 0.98, 95% CI: 0.26–3.74; p = 0.98). However, patients who underwent PCI had a higher risk of unplanned revascularization (SHR = 10.32, 95% CI: 2.42–43.95; p = 0.002). Conclusion: In patients with CAD with CTO, PCI was associated with a trend of lower short-term MACCE compared to CABG, but with a higher risk of long-term unplanned revascularization. There were no significant differences in long-term all-cause mortality, MACCE, or heart failure hospitalization rates between PCI and CABG.